Pan-American Highways: American Tourism to Mexico and 1950s Hollywood film - Stephanie Fuller (CINEJ Cinema Journal, 2014)
This article examines American films from the early 1950s which feature journeys to Mexico.  Movies such as Where Danger Lives (John Farrow, 1950), Gun Crazy (Joseph H. Lewis, 1950), Out of the Past (Jacques Tourneur, 1947) and Wetbacks (Hank McCune, 1954) present journeys to Mexico as escapes from American life in which romanticised freedom is closely connected to mobility and automobiles.  The article explores the connection between the films’ cinematic vistas of Mexican landscapes and American tourism to Mexico in this period.  Through their journeys to and across the border, these films call the wider relationship between the US and Mexico into question as national identities are constructed through travel, landscape and touristic encounters.